Perancangan Sistem Informasi Penjualan Busana Menggunakan Visual Basic (Studi Kasus Toko Original) - Yuliana Wea; Kristianus Jago Tute; Benediktus Yoseph Bhae (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Original store is a store engaged in the sale of clothing. The fashion sales information system that is being used to manage sales data is still using a manual system, where operational activities have not utilized the existing computer. Storage media is still using books so it is less efficient if there is a problem with the book. So the purpose of this study is to determine the design of a clothing sales information system using visual basic at the Original Store. This information system is designed using the Microsoft Visual Studio programming language and MySQL as the database. The method used is the SDLC (Software Development Life Cycle) method which consists of the stages of planning (Planning), analysis (Analysis), design (design), implementation (implementation), testing (testing) and management (maintenance). For system development method using descriptive qualitative method. As for testing using the Blackbox Testing method. Results to launch a better sales information system. So with the information system can provide information about the stock of goods, sales and reports based on a certain period in order to facilitate the owner in managing inventory.